6=x-4x+6

Simple and best practice solution for 6=x-4x+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6=x-4x+6 equation:


Simplifying
6 = x + -4x + 6

Reorder the terms:
6 = 6 + x + -4x

Combine like terms: x + -4x = -3x
6 = 6 + -3x

Add '-6' to each side of the equation.
6 + -6 = 6 + -6 + -3x

Combine like terms: 6 + -6 = 0
0 = 6 + -6 + -3x

Combine like terms: 6 + -6 = 0
0 = 0 + -3x
0 = -3x

Solving
0 = -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
0 + 3x = -3x + 3x
Remove the zero:
3x = -3x + 3x

Combine like terms: -3x + 3x = 0
3x = 0

Divide each side by '3'.
x = 0

Simplifying
x = 0

See similar equations:

| a+a-56=0 | | 13-x=-7-2x | | 4x+9-6x=9 | | B^2-10b+25=o | | x^2+2x+1+4x-64=0 | | -8x-4y=28 | | x+7+x=17 | | -2x-11=-2x-4 | | 5(6x-3)-3(3x-8)=5(4x+5)-22 | | 17/6-3/4+(-2/3) | | 6+3x+3x=66 | | (5a+9b)-(4b+2a)=0 | | 13-1/6 | | t+13t+40=0 | | 2x+3-5x=39 | | 4x+5=-177 | | 12.1-0.9z+2.3-1.2z=7-2.1z-7.2 | | 2299=11*11 | | 4x^2-16x=15 | | 2299=11*11*l | | 3v/v=v | | 14+7d+2d-8=16d+14-7d-8 | | 5y+3y-18=5y+5-3 | | 5x-1+2x=-22 | | 8y-18=5y+2 | | 1.2(z+4)-(6.6+0.2z)=-8+2 | | -16x+48=0 | | 5m^2n^3(mn^2)(4m-n)= | | (4.8x+15.5)+(2.1x-12.2)= | | 9n-6=81 | | 33r^2+38r-8= | | -2/3+3/4 |

Equations solver categories